Entotourism experiences for conservation awareness in Tawau Hills Park - Gao, Le (2021)
This research was conducted in Tawau Hills Park, Sabah aim to find out tourists’ perception and awareness about insects, and conservation potential through insects tourism. Four objectives were given, 1. To investigate group of insects that have potential to be promoted as nature tourism product in Tawau Hills Park; 2. To determine the viability of insect as nature tourism product in Tawau Hills Park; 3. To assess the potential of Entotourism in Tawau Hills Park; 4. To acquire a greater understanding of individuals’ perceptions on insects conservation and their awareness of insects. Two different methods were applied- survey about tourist’s perception and awareness of insects and tourism package activity in the field. SPSS was used for quantitative data analysis, while Leximancer was used to analyze the qualitative data. As Result, perceptions and awareness about insects should be evaluated base on these three main factors, value, knowledge and appearance. It indicated that there is little difference between demographics among tourists. Most participants responded positively about insects due to their special characteristics and importance. Beautiful insects such as butterfly, dragonfly, firefly get more attention by people, where other insects with interesting and rare have potential to explore. In terms of insect activity, Experience, Information, Booklet were three important factors should be concerned while conducting insects tourism. Tawau Hills Park was examined to have potential and viability in doing insects tourism. Participants are more willing to join insects activity with guided walk, experience insects in the field can help them to have better understating of learning insects. This study also brought a new opportunity to broaden and advance the scope of current and future plan ecotourism activity in similar area. Thus, aided to perceive positive perception amongst tourists towards entotourism activity especially insect species. Alternately, encourage the insect conservation action to publics. It provides methods and factors of promoting and developing entotorusim for entomologists, innovators, enthusiasts, tourism manager, park manager and government decision maker in the future.